HOW MOTHER'S EDUCATION SHAPE CHILDREN DEVELOPMENT IN INDONESIA? - Ida Ayu Meisthya Pratiwi; I Made Putra Yasa, Ni Kadek Sepiawati (Adisam Publisher, 2025)
Children’s development is a crucial factor in achieving the vision of Indonesia Emas 2045, particularly in fostering globally competitive human resources. One of the main challenges in realizing this vision is the high prevalence of wasting and stunting among children in Indonesia. As of 2023, the stunting prevalence in Indonesia recorded at 21.5%, indicating persistent issues with chronic malnutrition. Additionally, the wasting rate among children increased from 7.7% in 2022 to 8.5% in 2023. This research answers the question of how mother’s education can improving children's development. The research method uses quantitative analysis involving secondary data obtained from 2014 IFLS data. For the first equation, the dependent variable is stunting, measured by the height of children aged 0-5 years. For the second equation, the dependent variable is the weight of children aged 0-5 years. To ensure that the effects observed in the study are due to the independent variables of interest and not influenced by other external factors, we use some control variables, such as direct cash assistance, household income, waste management, number of household members, distance from home to healthcare facilities, area of residence (rural/urban), and ethnicity (Javanese/non-Javanese). The results of the analysis show that the mother’s education have significant and positive impact on height and weight of the children. Apart from that, the control variables of direct cash assistance, household waste management, and place of residence also have a positive effect on children's height as well as children weight. And house hold size have significant and negative relationship to height and weight of the children. This analysis shows the importance of mother’s education. Increasing mother's educational attainment can help increase family access, especially their children, to healthy nutrition, health services, hygiene and education, all of which can contribute to reducing stunting in children. There for, policy steps that support women's empowerment, such as increasing access to education and the economy for women as a mother for now and future need to be prioritized to reduce wasting and stunting of children in Indonesia.